A Matemática Financeira no Ensino Médio como fator de fomento da educação financeira: resolução de problemas e letramento financeiro em um contexto crítico - Kuntz, Eduardo Ribeiro (2019)
This research presents an investigation in the context of a qualitative research, aiming to promote aspects of Financial Education in High School. We conducted this study based on the question: Is it possible to promote the development of financial literacy and the awareness of some concepts of Financial Education in high school, through a didactic sequence built within the scope of Problem Solving? To this question, we bring a problematization of the theme from the available literature, official curricula and an analysis of the types of activities present in textbooks, in order to identify aspects that contribute to the discussion of the subject of study. Resulting from this problematization, this research proposed a sequence of activities based on the dialectics of action, formulation, validation and institutionalization present in the Theory of Didactic Situations, and built in light of the Didactic Strategy of Problem Solving, adopting the assumptions of Didactic Engineering. The sequence consisted of four activities that addressed the notions of increase, discount, simple interest and compound interest, seeking to relate these notions to problems of the social context. These activities were applied to a group of four junior high school students from a private school in the city of São Paulo. The results of this research indicate that, in these dialectics, according to the observation of the students' behavior in each activity, there was promotion of Financial Education. The study allows us to observe that the teacher, by institutionalizing the mathematical objects involved in each activity, fostered aspects of Financial Education, resorting to the students' answers, introducing them within a critical approach, encouraging them to reflect on the applicability of the objects. studied in your reality